Multifunctional electrospun nanofibrous scaffold enriched with alendronate and hydroxyapatite for balancing osteogenic and osteoclast activity to promote bone regeneration - Anjum, Shabnam; Arya, Dilip Kumar; Saeed, Mohammad; Ali, Daoud; Athar, Mohammad Saud; Yulin, Wang; Alarifi, Saud; Wu, Xixi; Rajinikanth, P.S.; Ao, Qiang (Frontiers in Bioengineering and Biotechnology, 2023)
Electrospun composite nanofiber scaffolds are well known for their bone and tissue regeneration applications. This research is focused on the development of PVP and PVA nanofiber composite scaffolds enriched with hydroxyapatite (HA) nanoparticles and alendronate (ALN) by the electrospinning technique. The developed nanofiber scaffolds were investigated for their physicochemical as well as bone regeneration potential. The results obtained from particle size, zeta potential, SEM and EDX analysis of HA nanoparticles confirmed their successful fabrication. Further, SEM analysis verified nanofiber's diameters within 200-250 nm, while EDX analysis confirmed successful HA and ALN incorporation into scaffolds. XRD and TGA analysis revealed the amorphous and thermally stable nature of the nanofiber composite scaffolds. Contact angle, FTIR analysis, Swelling and biodegradability studies revealed the hydrophilicity, chemical compatibility, suitable water uptake capacity and increased in-vitro degradation making it appropriate for tissue regeneration. The addition of HA into nanofiber scaffolds enhanced the physiochemical properties. Hemolysis, cell viability, cell adhesion and proliferation by SEM as well as confocal microscopy and live/dead assay results demonstrated the non-toxic and biocompatibility behavior of nanofiber scaffolds. Alkaline phosphatase (ALP) and tartrateresistant acid phosphatase (TRAP) assays demonstrated osteoblast promotion and osteoclast inhibition. These findings suggest that developed HA and ALN-loaded PVP/PVA-ALN-HA nanofiber composite scaffolds hold significant promise for bone regeneration applications.